Retinal nerve fiber layer in beta-thalassemia major: a comparative study - M. Firdous; M. F. Umer; S. P. Chandran (Российский офтальмологический журнал, 2025)
Beta-thalassemia is a hereditary blood disorder which occurs due to defective beta-globin gene synthesis. It is characterized by blood deficiency caused by ineffective erythropoiesis, hemolysis, and iron overload due to repeated transfusions. The purpose of the is study to find out the changes in retinal nerve fiber layer (RNFL) thickness as a result of Beta-thalassemia major and to compare the values with healthy individuals. Material and methods. This cross-sectional study was performed on a total of 56 beta-thalassemia major cases and 64 healthy controls from December 2023 to June 2024. The mean age of the cases (18.42 ± 4.05 years) and controls (17.45 ± 4.02 years) was significantly similar (p = 0.190). All the subjects undergone standard ophthalmological examination followed by RNFL thickness measurement using Heidelberg Spectralis OCT (Optical Coherence Tomography). Results. The RNFL thickness showed significant difference between the case and control groups. The p-value for global, inferior, nasal, and temporal RNFL thickness was < 0.001, while for superior RNFL p-value was 0.006. A significant correlation of global, inferior, and nasal RNFL measurements was found with the duration of thalassemia (p = 0.01, p = 0.01, p < 0.001), however, the global and nasal RNFL were found to be thinner in the cases receiving iron chelation monotherapy (p = 0.048, p = 0.006). Conclusion. The study concludes that the RNFL was significantly thinner in beta-thalassemia major cases in comparison to healthy controls. Moreover, only global, inferior, and nasal RNFL revealed to have a significant correlation with the thalassemia duration and iron chelation therapy.